Palmitoyl transferases have critical roles in the development of mosquito and liver stages of Plasmodium. (1st June 2016) - Hopp, Christine S.; Balaban, Amanda E.; Bushell, Ellen S. C.; Billker, Oliver; Rayner, Julian C.; Sinnis, Photini
Summary: As the Plasmodium parasite transitions between mammalian and mosquito host, it has to adjust quickly to new environments. Palmitoylation, a reversible and dynamic lipid post‐translational modification, plays a central role in regulating this process and has been implicated with functions for parasite morphology, motility and host cell invasion. While proteins associated with the gliding motility machinery have been described to be palmitoylated, no palmitoyl transferase responsible for regulating gliding motility has previously been identified. Here, we characterize two palmityol transferases with gene tagging and gene deletion approaches. We identify DHHC3, a palmitoyl transferase, as a mediator of ookinete development, with a crucial role for gliding motility in ookinetes and sporozoites, and we co‐localize the protein with a marker for the inner membrane complex in the ookinete stage. Ookinetes and sporozoites lacking DHHC3 are impaired in gliding motility and exhibit a strong phenotype in vivo ; with ookinetes being significantly less infectious to their mosquito host and sporozoites being non‐infectious to mice. Importantly, genetic complementation of the DHHC3‐ko parasite completely restored virulence. We generated parasites lacking both DHHC3, as well as the palmitoyl transferase DHHC9, and found an enhanced phenotype for these double knockout parasites, allowing insights into the functional overlap and compensational nature of the large family of PbDHHCs. These findings contribute to our understanding of the organization and mechanism of the gliding motility machinery, which as is becoming increasingly clear, is mediated by palmitoylation.